Respuesta :

First, factor the left side:

[tex](csc^2(x))^2-(cot^2(x))^2[/tex]

This can be simplified using [tex]x^2-y^2 = (x+y)(x-y)[/tex] where the csc term is x and the cot term is y:

[tex](csc^2(x)+cot^2(x))(csc^2(x)-cot^2(x))[/tex]

One of our Pythagorean Identities states that:

[tex]csc^2(x)-cot^2(x)=1[/tex]

So the left side is now:

[tex]csc^2(x)+cot^2(x)[/tex]

Now we can use the same Pythagorean Identity to change the right side to:

[tex]2csc^2(x)-(csc^2(x)-cot^2(x))[/tex]

All we did was express 1 in terms of csc and cot.

Distribute the negative:

[tex]2csc^2(x)-csc^2(x)+cot^2(x)[/tex]

Combine like terms:

[tex]csc^2(x)+cot^2(x)[/tex]

Now the left and right sides are the same.

Following are the proving to the given expression:

Given:

[tex]\bold{csc^4x-cot^4x=2csc^2x-1}[/tex]

To find:

Proving=?

Solution:

[tex]\to \bold{csc^4x-cot^4x=2csc^2x-1}[/tex]

Using formula:

[tex]\to (a^2-b^2)=(a-b)(a+b)[/tex]

Solving the L.H.S part:

[tex]\to \bold{csc^4x-cot^4x}\\\\\to \bold{(csc^2x)^2-(cot^2x)^2}\\\\\to \bold{(csc^2x-cot^2x) (csc^2x+cot^2x)}\\\\\therefore \\\\(csc^2x-cot^2x =1)\\\\(csc^2x-1 = cot^2x)\\\\\to \bold{1 (csc^2x+cot^2x)}\\\\\to \bold{(csc^2x+csc^2x-1)}\\\\\to \bold{( 2csc^2x-1)}\\\\[/tex]

Hence proved that L.H.S= R.H.S.

Learn more:

brainly.com/question/2292532

ACCESS MORE